1997
DOI: 10.1038/sj.bjp.0700945
|View full text |Cite
|
Sign up to set email alerts
|

NO/PGI2‐independent vasorelaxation and the cytochrome P450 pathway in rabbit carotid artery

Abstract: 1 The nature and cellular mechanisms that are responsible for endothelium-dependent relaxations resistant to indomethacin and N G -nitro-L-arginine methyl ester (L-NAME) were investigated in phenylephrine (PE) precontracted isolated carotid arteries from the rabbit. 2 In the presence of the cyclo-oxygenase inhibitor, indomethacin (10 mM), acetylcholine (ACh) induced a concentration-and endothelium-dependent relaxation of PE-induced tone which was more potent than the calcium ionophore A23187 with pD 2 values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 31 publications
9
50
1
Order By: Relevance
“…However, glibenclamide, a selective blocker of K ATP channels, had no effect. These results are consistent with those of Dong et al, 29 who demonstrated that vasorelaxation of rabbit carotid artery to acetylcholine is completely inhibited by CTX and is partially inhibited by apamin. A similar role for CTX and apamin-sensitive potassium channels in vasorelaxation to BK and acetylcholine has been demonstrated in a variety of other models.…”
Section: Figure 9 Effect Of Ksupporting
confidence: 83%
“…However, glibenclamide, a selective blocker of K ATP channels, had no effect. These results are consistent with those of Dong et al, 29 who demonstrated that vasorelaxation of rabbit carotid artery to acetylcholine is completely inhibited by CTX and is partially inhibited by apamin. A similar role for CTX and apamin-sensitive potassium channels in vasorelaxation to BK and acetylcholine has been demonstrated in a variety of other models.…”
Section: Figure 9 Effect Of Ksupporting
confidence: 83%
“…Moreover, the ACh-induced relaxation was completely prevented by L-NAME in the presence of high extracellular K + , suggesting that EDHF is released from endothelial cells and contributes to the endothelium-dependent relaxation. Similar observations have been made with the rabbit carotid artery and the rat renal artery [4,7].…”
Section: Discussionsupporting
confidence: 70%
“…Endothelial cells perform important paracrine functions. The vasoactive substances secreted by endothelial cells have been shown to affect function of other cells (3,4,7,10,11,15). Smooth muscle cells and endothelial cells are an immediate example of the communication between two different cell types.…”
mentioning
confidence: 99%